Social Support for People Living with Hiv Aids within the Accra Metropolitan Area - Agyir-Binn, H. (University of Ghana, 2005)
Social support has been identified as one o f the coping strategies in chronic illnesses especially in HIV/AIDS disease. The purpose of this study was to explore how the people living with HIV/AIDS (PLWHA) experience social support in the Accra Metropolitan area of Ghana. An exploratory, descriptive and qualitative method was employed in this study. A purposive sampling was used in the selection of the fourteen participants living with HIV/AIDS. They were interviewed using semi structured interview guide and observations. The data were analyzed using content analysis and constant comparison. The main themes that emerged from the study were; “Lived experiences o f PLWHA, biophysical experiences, psychological experiences, socio-economic, and socio-cultural experiences. Others included coping strategies, meaning attached to support, sources and types o f support, and perception o f support received. Other sub-themes emerged under these major themes. The findings indicated that the PLWHA experienced some unpleasant symptoms o f the disease, which limited their ability to work and earn income. This is because the disease has stigma attached to it, and it either made them weak and unable to work or has depleted their capital. A few were stigmatized and isolated by some members o f their family. This has created a variety of needs such as employment, getting the necessities o f life for themselves and their dependants and the need for healing o f their diseases. Each o f the participants had at least one support provider. These providers were; the family, community members, non-governmental organizations, church institutions, and health institutions. The support the participants received covered financial, assistance with basic needs, and social support. Others included medical, emotional and spiritual support. Whilst some o f these supports were provided spontaneously to the PLWHA, others had to beg for the support. It was the general view of all except one participant that the support they received was inadequate. The participants devised some coping strategies to contain the situation. Some o f these were projection, disclosure, and mutual support. Most o f them expressed their desire to work, preferably sedentary work. These findings have implications for nursing care and policy making. It is important for policy-makers to consider employment policies that would support the PLWHA to continue being employed, even after diagnosis, in jobs that do not entail strenuous activity. Policies on reaching out to the PLWHA should be intensified to prevent stigmatization and isolation o f the PLWHA.
Thesis(MPhil)-University of Ghana,2005